2017
DOI: 10.22492/ije.5.3.03
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pecha Kucha Presentations in the Assessment of a Translation Studies Unit at The University of Western Australia

Abstract: Results of a case study on the implementation of Pecha Kucha presentations undertaken at The University of Western Australia in 2015 are presented and discussed here. Pecha Kucha, a fast-paced presentation format consisting of 20 slides set to proceed automatically every 20 seconds, was used in the assessment of the unit "Translation Localisation" for two reasons: it is a time-effective method to assess a large number of students in a short time, and it has the potential to teach students whilst also assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…It was also evident from the findings that PK was challenging for some students as it requires learners to spend extra time and effort for preparation, the lack of which might lead to memorization of the presented material. The findings with respect to presentation skills are in accordance with those reported by several studies (e.g., Abraham et al, 2018;Colombi, 2017), in which PK was regarded as an effective way to improve students' presentation skills. Findings pertaining to the time and effort spent for preparation are also consistent with previous research (e.g., Angelina, 2019;Widyaningrum, 2016) with the exception of the study conducted by Beyer (2011) in a context featuring native English speakers.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It was also evident from the findings that PK was challenging for some students as it requires learners to spend extra time and effort for preparation, the lack of which might lead to memorization of the presented material. The findings with respect to presentation skills are in accordance with those reported by several studies (e.g., Abraham et al, 2018;Colombi, 2017), in which PK was regarded as an effective way to improve students' presentation skills. Findings pertaining to the time and effort spent for preparation are also consistent with previous research (e.g., Angelina, 2019;Widyaningrum, 2016) with the exception of the study conducted by Beyer (2011) in a context featuring native English speakers.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding PK's linguistic contributions, the findings of the present study demonstrated that learners had a perceived development in overall speaking, fluency, and pronunciation. A similar conclusion was reached by several studies which highlighted student experiences illustrating PK's contributions to their overall speaking skill (e.g., Angelina, 2019;Colombi, 2017) and fluency (Zharkynbekova et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations